Pengelolaan Id Card Pt. Internusa Cipta Solusi Perdana Menngunakan Sistem Berbasis Web - Dani; Dede Supriyadi; Achmad Lutfi Fuadi (Journal of Research and Publication Innovation, 2024)
Internusa Cipta Solusi Perdana or ICSP is an Indonesian Custom Software Developer that develops applications for various types of industry. ICSP has developed various application solutions that have a high level of difficulty that many other companies have. As an application developer, ICSP has the advantage of customizing applications that can be adapted to the needs and business processes of ICSP customers. Information developments are currently increasing, in society, information technology covers almost all areas, including companies. In fact, it is a necessity for companies to have computerized information available. Almost all companies now use identity cards or ID cards for their employees. as an identity that differentiates it from other companies, there are many benefits to be gained from using an ID card system that is integrated with company attendance and databases because this can increase employee motivation and performance, however we very rarely find the use of ID cards in universities, especially at PT. INTERNUSA CIPTA SOLUSI PERDANA, I don't know if it's because they don't have an ID card yet or they already have one but are still reluctant to use it. The hope is that making an ID card that uses barcodes will attract interest in using it. Making this ID card uses a website-based system.